One-half century (or more) of study of cell death: origins, present, and perhaps future - Lockshin, Richard A. (Frontiers in Cell Death, 2023)
The concept of biological cell death—that is, cell death that is neither accidental nor chaotic—has existed and has been obvious since at least the beginning of the 20th C, but it was noticed by other than specialists apt choices of words that caught the spirit of the time, “programmed cell death” and “apoptosis” caught the attention of a wider range of scientists. Then, by the early 1990s the recognition of at least two genes that were important to cancer and other diseases by controlling cell death (p53, Bcl-1, and Fas); recognition that cell death could be controlled by a highly conserved family of proteases; and the development of rapid and easy means of measuring cell death, led to the explosion of the field as a subject of research. Today we recognize many variations on the theme of biological cell death, but many mysteries remain. The most important of these remaining mysteries is that we recognize many of the penultimate and ultimate steps to kill cells, but it is rarely clear how and why these steps are activated. Most likely they are activated by an interaction of several metabolic steps, but we will need more high-powered analysis to determine how this